2014
DOI: 10.1007/s10071-014-0776-6
|View full text |Cite
|
Sign up to set email alerts
|

Practice makes proficient: pigeons (Columba livia) learn efficient routes on full-circuit navigational traveling salesperson problems

Abstract: Visiting multiple locations and returning to the start via the shortest route, referred to as the traveling salesman (or salesperson) problem (TSP), is a valuable skill for both humans and non-humans. In the current study, pigeons were trained with increasing set sizes of up to six goals, with each set size presented in three distinct configurations, until consistency in route selection emerged. After training at each set size, the pigeons were tested with two novel configurations. All pigeons acquired routes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Our data showed that the reintroduced macaws added about five new tree species to their diet per month and that trees of many of these species were highly dispersed. This suggests that they were probably using and expanding a cognitive map regarding the spatial and temporal location of food resources in the release area, such as has been reported in other birds [40], and it is possible that their foraging may have also been based on random exploratory movements resulting from tree-scale foraging experiences [41]. Bearing in mind the above and the short duration of our study, it is likely that our data set is an underestimate of food species that the reintroduced macaws use as a source of food.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that the reintroduced macaws added about five new tree species to their diet per month and that trees of many of these species were highly dispersed. This suggests that they were probably using and expanding a cognitive map regarding the spatial and temporal location of food resources in the release area, such as has been reported in other birds [40], and it is possible that their foraging may have also been based on random exploratory movements resulting from tree-scale foraging experiences [41]. Bearing in mind the above and the short duration of our study, it is likely that our data set is an underestimate of food species that the reintroduced macaws use as a source of food.…”
Section: Discussionmentioning
confidence: 99%
“…A third approach to navigational TSP is to examine the role of learning and memory in route optimization by testing animals that can solve the task over multiple trials. In this context, rats (Bures et al 1992), pigeons (Baron et al 2015), and bees (Lihoreau et al 2012) can all develop efficient paths to navigate between mul-tiple locations. For instance, bumblebees allowed to forage for several hours in an array of artificial flowers typically find the shortest possible routes to visit all flowers once and return to the nest.…”
Section: Navigational Tspmentioning
confidence: 99%
“…Given the economics of traveling across varying distances for resources (e.g., Kacelnik & Cuthill, 1987) many animals faced with these problems would also be expected to choose efficient routes. Researchers have been investigating if animals, including insects (Lihoreau et al, 2012), rodents (Bellizzi et al, 2015;Blaser & Ginchansky, 2012), birds (Baron et al, 2014;Gibson et al, 2007;Miyata & Fujita, 2010), and primates (Janson, 2007;MacDonald & Wilkie, 1990;Noser & Byrne, 2010), can efficiently solve TSPs.…”
Section: Introductionmentioning
confidence: 99%